Pedagogy Beyond Piracy: Un-Learning the White Body to Recreate a Body of Learning - Perkinson, James W. (Teaching theology and religion, 2012)
This essay highlights a range of questions that arise when white suburban students engage urban neighborhoods of poverty and color in the United States. How can involvement in an “other” context move beyond “educational tourism”? The essay presents a pedagogical style that raises questions of the kind of socialized body one inhabits: either one shaped by presumptions of control and rights of academic observation, or one mobilized to risk involvement in a differently communalized episteme. And while the pedagogy described may not be replicable by faculty who do not share the author's background or cross-cultural orientation, the rhetorical style of the essay itself enacts the tensions that this pedagogy contends with: the efforts of a white male educator – altered by decades of inner city involvement – to open “white” space in the classroom to other norms of embodiment and other modes of learning. Here is the necessity and impossibility of moving beyond “educational tourism.”